Analisis Strategi Belajar dan Manajemen Waktu pada Mahasiswa yang Bekerja di UIN Walisongo Semarang - Rufaeda, Jazala Jihan; Lestari, Sri Ayu; Aini, Dewi Khurun (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out a general picture of time management and study strategies used by students who are working and to find out how students manage their time well between work and study. This research is a type of qualitative research using the interview method. The informants in this research were students at UIN Walisongo Semarang who were working. The interview results are strengthened by very relevant research literature. This research shows that the results of students who study while working have different learning strategies and time management skills for each individual. The time management skills used are (1) making daily and weekly schedules, (2) trying to ignore things that bother them. focus, (3) commitment to goals. And the learning strategies used are (1) making a task schedule, (2) repeating the material again, (3) overnight speed system.